Non-linear processes in shallow waters. Influence on local observed mean sea level - De Toro, C.; Gil, E. (Física de la Tierra, 2005)
A combined theoretical and empirical method is applied to study the nonlinear interactions occurring in shallow waters among astronomical, overtide and compound constituents. Although the isolated nonlinear terms present a small amplitude, the global response of the oceans to the primary and secondary interactions can mean an important contribution to the sea level variability in continental shelf and coasts with a strong tidal signal. Thus, an accurate determination inside these areas is of considerably importance both in mean sea level studies and in tidal prediction. To this purpose, a formal theoretical development of the generating processes has been accomplished. At the same time, the tidal parameters of the most significant shallow water constituents have been empirically determined in six nearby stations located in the Cantabric Sea. The methodology developed for this determination and later elimination of over and compound tides is described in this work. Besides, the simultaneous determination allows us to study the dependence of these non primary waves on the properties of the emplacements. The effectivity of the method has been contrasted through an iterative process based on spectral analysis of the residuals. The application, component by component, of this technique, allows us to minimize the influence of tidal forces on mean sea level, as it is shown in the increased accuracy.